GE11 peptide-decorated acidity-responsive micelles for improved drug delivery and enhanced combination therapy of metastatic breast cancer. Issue 44 (7th November 2022) - Guo, Zhihao; Sui, Junhui; Li, Yumei; Wei, Qinchuan; Wei, Cailing; Xiu, Linyun; Zhu, Ruohua; Sun, Yong; Hu, Jianshe; Li, Ji-Liang
Abstract : GE11-decorated polycarbonate-DOX conjugate micelles enhance tumor-targeted drug delivery and precisely controlled release, thereby inhibiting tumor growth and metastasis. Abstract : Nanotechnology-mediated drug delivery systems suffer from insufficient retention in tumor tissues and unreliable drug release at specific target sites. Herein, we developed an epidermal growth factor receptor-targeted multifunctional micellar nanoplatform (GE11-DOX+CEL-M) by encapsulating celecoxib into polymeric micelles based on the conjugate of GE11-poly(ethylene glycol)- b -poly(trimethylene carbonate) with doxorubicin to suppress tumor growth and metastasis. The polymeric micelles maintained stable nanostructures under physiological conditions but quickly disintegrated in a weakly acidic environment, which is conducive to controlled drug release. Importantly, GE11-DOX+CEL-M micelles effectively delivered the drug combination to tumor sites and enhanced tumor cell uptake through GE11-mediated active tumor targeting. Subsequently, GE11-DOX+CEL-M micelles dissociated in response to intracellular slightly acidic microenvironmental stimuli, resulting in rapid release of celecoxib and doxorubicin to synergistically inhibit the proliferation and migration of tumor cells. Systemic administration of GE11-DOX+CEL-M micelles into mice bearing subcutaneous 4T1 tumor models resulted in higher tumor growth suppression and decreased lung metastasis of tumor cells compared with micelles without GE11 decoration or delivering only doxorubicin. Furthermore, the micelles effectively reduced the systemic toxicity of the chemotherapy drugs. This nanotherapeutic system provides a promising strategy for safe and effective cancer therapy.